Green national accounting: Synthesising and extending the welfare based and sustainability-standard based approaches - Anil Markandya; Pamela Mason; Marialuisa Tamborra (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper examines the theoretical foundations of Green National Accounting, noting that their assumptions have led to green national income measuring welfare-based income, which is not necessarily equal to sustainable income. We review two major approaches to estimating green accounting: the welfare-based GARP approach provides the values of environmental damage to estimate the net welfare generated by economic activity and the GREENSTAMP approach calculates the economic output compatible with achieving environmental sustainability. Both approaches deliver policy-relevant information and a comparison of the results obtained using both methods illustrates this. The GARP approach facilitates the identification of efficient level of environmental protection, while the GREENSTAMP approach identifies the costs of meeting sustainable standards. These distinct advantages suggest that the two approaches could be fruitfully synthesised, and this paper outlines how this could be achieved. The appropriate choice is likely to be informed by the results of the current revision of the UN SEEA.
Keywords: Q2; Q3; O47; 330; Green national accounting; welfare; sustainability; Umweltökonomische Gesamtrechnung; Wohlfahrtsanalyse; Nachhaltige Entwicklung; EU-Staaten; Tschechische Republik